Prediction of Simulated 1,000 m Kayak Ergometer Performance in Young Athletes - Coelho, André B.; Nakamura, Fábio Y.; Morgado, Micaela C.; Alves, Francisco; Di Baldassarre, Angela; Flatt, Andrew; Rama, Luis (Frontiers in Public Health, 2021)
This study aimed to develop a predictive explanatory model for the 1,000-m time-trial (TT) performance in young national-level kayakers, from biomechanical and physiological parameters assessed in a maximal graded exercise test (GXT). Twelve young male flat-water kayakers (age 16.1 ± 1.1 years) participated in the study. The design consisted of 2 exercise protocols, separated by 48 h, on a kayak ergometer. The first protocol consisted of a GXT starting at 8 km.h−1 with increments in speed of 1 km.h−1 at each 2-min interval until exhaustion. The second protocol comprised the 1,000-m TT. Results: In the GXT, they reached an absolute V∙O2max of 3.5 ± 0.7 (L.min−1), a maximum aerobic power (MAP) of 138.5 ± 24.5 watts (W) and a maximum aerobic speed (MAS) of 12.8 ± 0.5 km/h. The TT had a mean duration of 292.3 ± 15 s, a power output of 132.6 ± 22.0 W and a V∙O2max of 3.5 ± 0.6 (L.min−1). The regression model [TT (s) = 413.378–0.433 × (MAP)−0.554 × (stroke rate at MAP)] presented an R2 = 84.5%. Conclusion: It was found that V∙O2max, stroke distance and stroke rate during the GXT were not different from the corresponding variables (V∙O2peak, stroke distance and stroke rate) observed during the TT. The MAP and the corresponding stroke rate were strong predicting factors of 1,000 m TT performance. In conclusion, the TT can be useful for quantifying biomechanical parameters (stroke distance and stroke rate) and to monitor training induced changes in the cardiorespiratory fitness (V∙O2max).